Populism and Foreign Policy: An Assessment and a Research Agenda - Onderco, Michal (Journal of Regional Security, 2020)
Populist parties are often seen as a threat to liberal democracy domestically, and in the international arena, they are often accused of unwillingness to support a liberal international order. We study how what we know about foreign policy preferences of populist parties is driven by how we study the phenomenon; and how we can fix the shortcomings which exist in the literature. To sketch a future research agenda, we first conduct a systematic review of the literature on the foreign policy views of populist parties in Europe and investigate how what we know is driven by how we know it. We look at the themes of foreign policy, research methods, as well as the parties and countries in researchers’ focus. Our findings indicate that skewed focus on particular countries and parties combined with a uniform use of methods contributes to a lack of detailed understanding of populist views on foreign policies. We propose future avenues of research into the foreign policy views of populist parties, including a diversification of methods and more in-depth empirical and cross-national studies on specific themes.